Improving Medical Students' OSCE Performance in Telehealth: The Effects of a Telephone Medicine Curriculum. (December 2020) - Hindman, Daniel J.; Kochis, Suzanne R.; Apfel, Ariella; Prudent, Joshua; Kumra, Tina; Golden, W. Christopher; Jung, Julianna; Pahwa, Amit K.
Abstract : Purpose: To report on the implementation of a telephone medicine curriculum as part of the core clerkship in pediatrics for students at Johns Hopkins University School of Medicine and evaluate the curriculum's effect on student performance on a telephone medicine case as part of a required objective structured clinical exam (OSCE). Method: Using a prospective cohort design with a convenience sample of third-year medical students during the 2016–2017 and 2017–2018 academic years, the authors compared the OSCE scores of students assigned to the curriculum with both historical and concurrent control groups of students who had not received the curriculum. Additionally, the authors compared the costs of the recommended testing by students in each group using the 2018 Centers for Medicare and Medicaid Services Clinical Laboratory Fee Schedule. Results: Students assigned to the telephone medicine curriculum (students in the intervention group) had a significantly higher mean overall score on the simulated OSCE telephone medicine case compared with the students in the control groups who did not receive the curriculum (the mean score for students in the intervention group was 7.38 vs 6.92 for students in the control groups, P = .02). Additionally, the intervention group had statistically significantly lower costs for their recommended testing compared with the control groups (the median value for tests ordered by students in the intervention group was $27.91 vs $51.23 for students in the control groups, P = .03). Conclusions: Implementing a dedicated telephone medicine curriculum for medical students improves their overall performance and delivery of high-value care via telephone medicine as part of an OSCE. Medical educators should pursue ongoing research into effective methods for teaching medical students and residents how to navigate digital encounters.